Progeny Evaluation of Melia Azedarach (linn.) for Leaf Senescence, Fruit Characters and Wood Specific Gravity - Meena, Himanshu; Sharma, Rajni; Kumar, Ashok (Indian Forester, 2014)
Fifty four progenies of Melia azedarach (Linn.) from eleven geographical locations were evaluated for leaf senescence, fruit characters and wood specific gravity. Large variations were recorded for leaf senescence period ranged from 35 to 119 days per year in 8-year-old progeny trial, however, few progenies remained semi-evergreen. Between progeny and within progeny differences were found significant. The narrow sense heritability (progeny basis, within progeny basis and individual plant basis) was calculated for all the characters. High heritabilities were recorded for fruit characters and specific gravity. Fruit characters have high genetic gain, whereas, specific gravity has low genetic gain. Genetic gain for within family selection was higher than family selection for all traits.